2021
DOI: 10.1021/acsaelm.1c00161
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a TiN Capping Layer on Phase Transformation and Capacitance Enhancement in ZrO2

Abstract: Tailoring of crystalline phases and dielectric properties of ZrO2 thin films are demonstrated by capping a nanoscale TiN layer prepared by plasma-enhanced atomic layer deposition. The in-plane tensile strain induced by the TiN capping layer gives rise to the dramatic paraelectric-to-antiferroelectric phase transformation in ZrO2 and the significant capacitance enhancement up to 209%. The result is attributed to the formation of the ZrO2 tetragonal phase with the out-of-plane compressive strain due to TiN cappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…According to the International Center for Diffraction Data (ICDD), the diffraction from the crystalline planes in the tetragonal ( t (101), 2θ = 30.223°, JCPDS card 79-1769), orthorhombic ( o (111), 2θ = 30.133°, JCPDS card 79-1796), and cubic ( c (111), 2θ = 30.120°, JCPDS card 49-1642) phases of ZrO 2 is all around 2θ ∼ 30.5°. Because of the high dielectric constant, the presence of the cubic, orthorhombic, or tetragonal phase in ZrO 2 is very beneficial for the EOT scaling. As compared with the Z0 sample, the emergence of the diffraction peak in the Z0T sample can be attributed to the TiN capping layer effect, which produces the in-plane tensile stress to induce the ZrO 2 crystallization. Notice from Figure that the crystallization of ZrO 2 is mainly caused by the TiN capping layer effect, not by the ALA treatment. No diffraction peak can be observed in the Z0 and ZA samples, which manifests that only the ALA treatment is not able to induce the ZrO 2 crystallization.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the International Center for Diffraction Data (ICDD), the diffraction from the crystalline planes in the tetragonal ( t (101), 2θ = 30.223°, JCPDS card 79-1769), orthorhombic ( o (111), 2θ = 30.133°, JCPDS card 79-1796), and cubic ( c (111), 2θ = 30.120°, JCPDS card 49-1642) phases of ZrO 2 is all around 2θ ∼ 30.5°. Because of the high dielectric constant, the presence of the cubic, orthorhombic, or tetragonal phase in ZrO 2 is very beneficial for the EOT scaling. As compared with the Z0 sample, the emergence of the diffraction peak in the Z0T sample can be attributed to the TiN capping layer effect, which produces the in-plane tensile stress to induce the ZrO 2 crystallization. Notice from Figure that the crystallization of ZrO 2 is mainly caused by the TiN capping layer effect, not by the ALA treatment. No diffraction peak can be observed in the Z0 and ZA samples, which manifests that only the ALA treatment is not able to induce the ZrO 2 crystallization.…”
Section: Resultsmentioning
confidence: 94%
“…The extracted density and thickness of the ZrO 2 thin films are shown in Figure (c). One can see that the TiN capping layer effect contributes to a significant increase in the ZrO 2 film density (4.99 g/cm 3 for Z0 vs 5.39 g/cm 3 for Z0T and 5.23 g/cm 3 for ZA vs 5.51 g/cm 3 for ZAT), which is ascribed to an increase of the ZrO 2 crystallinity due to the stress induced by the TiN capping layer. The film density of the ZrO 2 layers is also increased by the ALA treatment (4.99 g/cm 3 for Z0 vs 5.23 g/cm 3 for ZA and 5.39 g/cm 3 for Z0T vs 5.51 g/cm 3 for ZAT), indicating that the adatom migration enhanced by the in situ ALA treatment results in the film densification of ZrO 2 . The incidence of plasma species during the ALA treatment also generates compressive stress in the out-of-plane direction, resulting in an increase in the film density. , An increase in the film density is usually accompanied by a reduction in the defect density. A decrease in the amount of oxygen vacancies by the ALA treatment has been confirmed by the O 1s X-ray photoelectron spectroscopy of the ZrO 2 layers, which has been revealed in our previous work. , Upon the TiN capping layer effect and the ALA treatment, the ZrO 2 film density was effectively increased to approach that of the bulk ZrO 2 (5.68 g/cm 3 ) …”
Section: Resultsmentioning
confidence: 99%
“…The slight double peak is observed in the single ZrO 2 sample. In contrast, the ZTO samples exhibit two pairs of butterfly-like dielectric constant peaks due to polarization switching. ,, In addition, the dielectric constant at 0 V bias increases with the Ti proportion in the ZTO thin films, which is related to the formation of the T-phase. , …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that lower process temperature could inhibit the formation of M-phase, thus boosting the AFE properties of the films. On the other hand, the PEALD process modifies the surface through plasma exposure, which can be used to improve nucleation and adhesion, thereby enhancing the formation of a denser film . By adjusting Ti or Ti/Si doping in the ZrO 2 dielectric, both the ZTO and ZTSO capacitors are investigated for energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation